2022
DOI: 10.14218/jcth.2022.00244
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Hepatitis of Unknown Origin in Children: What Do We Know Today?

Abstract: In May 2022, the UK International Health Regulations National Focal Point notified World Health Organization of 176 cases of severe acute hepatitis of unknown etiology in children under 10 years of age. From that moment on, cases of severe acute hepatitis of unknown origin in children began to be reported in several countries. As of June 17, 2022, a total of 991 cases had been reported in 35 countries worldwide, 50 children needed a liver transplant and 28 patients died. According to information published by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
8
0
6
Order By: Relevance
“…(280) of these cases are from the United Kingdom of Great Britain and Northern Ireland alone, followed by Spain (54 cases), Italy (50), Ireland (29), Portugal (28), Poland (23), Greece (21), the Netherlands (16), Belgium (14), Sweden (12) and France (10). 17 The second highest number of probable cases and cases pending classification has been reported from the Region of the Americas (435), including 334 cases (33% of global cases) from the United States of America, followed by the Western Pacific Region (70 cases), the South-East Asia Region (19) and Eastern Mediterranean Region.…”
Section: Epidemi Ologymentioning
confidence: 99%
See 1 more Smart Citation
“…(280) of these cases are from the United Kingdom of Great Britain and Northern Ireland alone, followed by Spain (54 cases), Italy (50), Ireland (29), Portugal (28), Poland (23), Greece (21), the Netherlands (16), Belgium (14), Sweden (12) and France (10). 17 The second highest number of probable cases and cases pending classification has been reported from the Region of the Americas (435), including 334 cases (33% of global cases) from the United States of America, followed by the Western Pacific Region (70 cases), the South-East Asia Region (19) and Eastern Mediterranean Region.…”
Section: Epidemi Ologymentioning
confidence: 99%
“…4 But, despite strong incentives and advice for member states by WHO to report cases of severe acute hepatitis of unknown aetiology in children, the question remains whether there have been patients with milder cases of hepatitis which have not been reported. 16 Although major points are similar, the issue remains that the used case definitions of severe acute hepatitis of unknown aetiology in children are quite different by criteria for age and time of presentation, and that the question is how much such variations impact the identification of cases and contribute to the differences in the frequency of the disease. A lack of a unified, standardised case definition is not facilitative for classification and statistics estimates.…”
Section: The Cour S E Of the D Is E A S Ementioning
confidence: 99%
“…Perez-Gracia et al found that approximately half of patients tested positive for adenovirus according to while blood specimens. However, none tested positive according to liver and plasma samples (7). These findings lessen adenovirus as a potential etiology of SHIC.…”
mentioning
confidence: 75%
“…First, while typically self-limiting in healthy adults, HAdV can induce severe disease in certain populations, such as pediatric, geriatric, and immunocompromised individuals (including those on immunosuppressants) [ 158 , 159 , 160 , 161 ]. For example, recently, HAdV has received significant notoriety for its potential involvement in a mysterious outbreak of severe acute hepatitis of unknown origin that has been diagnosed in over 650 children from 33 countries around the world (reviewed in [ 162 , 163 ]). Despite the potential for significant HAdV-induced disease in infected patients, there are still no approved therapeutics for HAdV [ 151 ].…”
Section: Discussionmentioning
confidence: 99%